The Role of Philosophy in the Development of Islamic Education Management (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research has the aim of how we can find out the importance of the role of philosophy in the management of Islamic education. This research uses qualitative methods with a library approach and literature related to the theme. From the results of the author's analysis, philosophers have a strong role in contributing to the development of Islamic education management, including thinking in terms of ontology, epistemology and axiology, as well as maintaining how Islamic education management science is able to plan, organize, mobilize and provide good control,  because Islamic education management will develop well by strengthening Islamic values ​​in educational institutions guided by the Qur’an and Hadith, because that’s by knowing it is history, development of philosophy and management science, then understanding the schools of philosophy, both classical philosophy and modern philosophy, and knowing how much the philosophers have contributed to the development of management science in Islamic education today.